A paradox of latitudinal leaf defense strategies in deciduous and evergreen broadleaved trees. Issue 5 (1st June 2018) - Saihanna, Saihanna; Tanaka, Tomoe; Okamura, Yu; Kusumoto, Buntarou; Shiono, Takayuki; Hirao, Toshihide; Kubota, Yasuhiro; Murakami, Masashi
Abstract: The classical "low latitude–high defense" hypothesis is seldom supported by empirical evidence. In this context, we tested latitudinal patterns in the leaf defense traits of deciduous broadleaved (DB) and evergreen broadleaved (EGB) tree species, which are expected to affect herbivore diversity. We examined the co‐occurrence of leaf defense traits (tannin and phenol content, leaf mechanical strength, leaf dry matter content, leaf mass per area, and leaf thickness) in 741 broadleaved tree species and their correlations with species geographical range in East Asian island flora. We discovered contrasting latitudinal defense strategy gradients in DB and EGB tree species. DB species employed chemical defenses (increasing tannin and phenol content) at higher latitudes and physical defenses (softer and thinner leaves) at lower latitudes, whereas EGB tree species exhibited opposite latitudinal defense patterns. The "low latitude high defense" hypothesis included a paradoxical aspect in chemical and physical defense traits across broadleaved tree species. To reconcile paradoxical defense strategies along the latitudinal gradient, we conclude that interactive correlations among leaf traits are controlled by leaf longevity, which differs between DB and EGB tree species.